Study of the Noise Reduction of DF9S1600 Gearbox Reverse Gear - Li Haiqing (Jixie chuandong)
Taking the reverse gear of DF9S1600 gearbox as study object,by using the advanced computer simulation technology,through the method of the combination of finite element and boundary element,the systematic study of reverse gear is carried out. Based on multi-body dynamics theory,by using SolidWorks software,a solid model gear transmission is built and by using ANSYS software meshing,gear transmission model achieves flexible,the modal analysis is completed. The meshing modal analysis for reverse gear,two shaft reverse gear,reverse gear and the intermediate shaft are carried out by using ANSYS software,the maximum stress is 0. 164 9 MPa,and the equivalent elastic strain is 8. 265 × 10-7mm for two gears meshing. The maximum stress is 0. 481 9 MPa,the maximum equivalent elastic strain is 3. 071 5 × 10-6mm for the intermediate reverse gear shaft. It is full-compliance with the requirements. And according to the test,the effects of reverse gear noise is analyzed respectively from the speed,load and gear manufacturing errors,the structure is improved to achieve the purpose of the reverse gear damping noise reduction.